A Comparative Review of Animal Models of Middle East Respiratory Syndrome Coronavirus Infection. (May 2016) - Baseler, L.; de Wit, E.; Feldmann, H.
Middle East respiratory syndrome coronavirus (MERS-CoV) was initially isolated from a Saudi Arabian man with fatal pneumonia. Since the original case in 2012, MERS-CoV infections have been reported in >1500 humans, and the case fatality rate is currently 35%. This lineage C betacoronavirus has been reported to cause a wide range of disease severity in humans, ranging from asymptomatic to progressive fatal pneumonia that may be accompanied by renal or multiorgan failure. Although the clinical presentation of human MERS-CoV infection has been documented, many facets of this emerging disease are still unknown and could be studied with animal models. Several animal models of MERS-CoV have been developed, including New Zealand white rabbits, transduced or transgenic mice that express human dipeptidyl peptidase 4, rhesus macaques, and common marmosets. This review provides an overview of the current state of knowledge on human MERS-CoV infections, the probable origin of MERS-CoV, and the available animal models of MERS-CoV infection. Evaluation of the benefits and limitations of these models will aid in appropriate model selection for studying viral pathogenesis and transmission, as well as for testing vaccines and antivirals against MERS-CoV.